Rancang Bangun Aplikasi Web Dinamis Untuk Pemasaran Tanaman Hias Bonsai Pada Paguyuban Sekarsari - Daniel Yeri Kristiyanto; Bambang Suhartono (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
Paguyuban bonsai ornamental plant is a premium ornamental plant, it becomes interesting if its marketing adopts information technology while aligning the goals of its members. The modern web concept is dynamic and responsive used to support the marketing activities of ornamental plant farmers through object oriented based design. This web design uses the Waterfall method using five main stages and fifteen subwork items. All sub items of work are estimated based on a triple time estimate that has a variable start time, actual time, and late time. Estimation of bonsai dynamic web marketing projects takes 115 days of 95%, the potential of the project to finish 111 days earlier by 2,5%, and the potential of the project to be 118 days late by 2,5%. Modelling using Waterfall produces a standart error of 0,0509 smaller than the standart deviation of 1,9, so it can be said that this model is very good and representative to be carried out according to the specified time. Bonsai ornamental plant marketing websites have use responsive concepts using PHP MVC Framework and dynamic concepts using bootstrap.